Demystifying the Puzzle of Applied Communications Research - Mark Tucker; Stan Ernst; Coreen E. Henry (Journal of Applied Communications, 2004)
While research capabilities in agricultural and applied communications have increased substantially in recent years, there is still room for improvement. The shortcomings in applied communications research result largely from confusion and misunderstanding about the research process. As an alternative to the technical treatments provided in conventional research methods textbooks, this paper proposes a user-friendly “puzzle” schema to help practitioners understand and address the essential elements in planning applied communications research. The authors provide an overview of the framework and its component parts, followed by a brief discussion of common myths surrounding the research process. A central point is that bypassing or truncating essential research components can jeopardize the validity of findings in applied communications research. The approach advocated here differs from conventional methodology approaches in that it allows for more fluidity in the research planning process. Recommendations for improving the applied communications research base are provided for both individuals and the profession as a whole.